2014
DOI: 10.1155/2014/484120
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Hydrometeorological Forecasts Using WRF Hourly QPF and TopModel for a Middle Watershed

Abstract: Quantitative precipitation forecasts (QPFs) were obtained from ensembles of the weather and research forecasting (WRF) model for the Iguaçu river watershed (IRW) in southern Brazil. Thirty-two rainfall events between 2005 and 2010 were simulated with ten configurations of WRF. These rainfall events range from local to synoptic scale convection and caused a significant increase in the level of the Iguaçu river. In the average, the ensembles yielded up to 20% better skill than single WRF forecasts for the events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
(38 reference statements)
2
22
0
Order By: Relevance
“…Higher skill of the ensemble mean in comparison with deterministic forecasts has also been found in other flood forecasting systems driven by the WRF model (Calvetti et al, 2014) and other NWP models (Vincendon et al, 2011).…”
Section: Evaluating Discharge Forecastsupporting
confidence: 56%
“…Higher skill of the ensemble mean in comparison with deterministic forecasts has also been found in other flood forecasting systems driven by the WRF model (Calvetti et al, 2014) and other NWP models (Vincendon et al, 2011).…”
Section: Evaluating Discharge Forecastsupporting
confidence: 56%
“…The first examples of ESF for Brazilian cases are shown by Tucci et al (2003 and2008), who showed results of hindcasting experiments of seasonal streamflow forecasts for the rivers Uruguay and Grande. More recently, Calvetti and Pereira (2014), Collischonn et al (2013) and Meller (2013) described experiments of short-to medium-range ensemble flood forecasting. Fernández Bou et al (2015) showed the development of a methodology for 1-month flood forecasting in the upper region of the Uruguay River basin, at the Itá Hydroelectric Power Plant (HPP) reservoir.…”
mentioning
confidence: 99%
“…The complexity involved in forecasting is extensive, and precipitation has the most complex behavior compared to other meteorological forecasts. Errors in NWP model forecasts are caused by incomplete and inaccurate observations of data assimilation and escalated by the model's dynamic and physical approximations [8]. Although several studies have During the summer, South and North Korea experience torrential rainfall and storms, as has been reported in previous studies [22].…”
Section: Introductionmentioning
confidence: 94%